Effects of aerobic exercise on the components of metabolic syndrome in the older population with type 2 diabetes mellitus: a systematic review and meta-analysis - Miranda-Tueros, Mercedes (2024)
Objectives. To determine the effects of aerobic exercise on the components of the metabolic syndrome in older diabetic patients. Materials and methods: We used the PubMed/Medline, Scopus, Cochrane library, Web of Science databases and the Google Scholar search engine. Randomized controlled trials ( RCTs ) were selected according to the inclusion criteria. Two review authors independently determined whether studies met the inclusion criteria, extracted data and used the Cochrane risk of bias (ROB 2.0) tool. Quantitative analyzes were performed in R V. 4.0.5 using random effects. Results. The searches identified 8697 studies, of which 7 RCTs were included in the qualitative synthesis. Most studies were assessed to have high or low ROB in at least three domains. The meta-analysis showed that aerobic exercise was effective in improving glucose levels (standardized mean difference [SMD]: -1.04; 95% confidence interval [CI]: -1.27, -0.81), systolic blood pressure ([SMD]: -0.79; [CI]: -1.02; -0.56), diastolic blood pressure ([SMD]: -0.75; [CI]: -0.98; -0.52), glycosylated hemoglobin ([SMD]: -0.57, [CI]: -0.77, -0.37), HDL ([SMD]: 0.35, [CI]: 0,15 ; 0.55), triglycerides ([SMD]: -0.26; [CI]: -0.47; -0.06). No significant adverse effects were reported. Conclusions. Aerobic exercise was shown to have a significant improvement in the components of the metabolic syndrome in diabetic older adults and no significant adverse effects were reported. However, we recommend more RCTs with a longer intervention time to establish the impact on symptoms and complications.